Pengaruh Luas Kebakaran Hutan dan Lahan Terhadap Tingkat Pencemar Udara PM10 - Dwi Maharani; Dewi Arafa Azra; Sarah Aprilia; Uzzi Ziqma; Resa Septiani Pontoh (ECOTAS, 2021)
Land and forest fires that took place in the Indonesian Province will produce some substances that can pollute the air. The air pollution is monitored by the Air Pollution Standard Index or ISPU which consist of a concentration value of 5 kinds of substances as parameters, such as particulate (PM10), carbon monoxide (CO), sulfur dioxide (SO2), nitrogen dioxide (NO2), and ozone (O3). The causes of land and forest fires vary, it could be due to nature and humans. Forest fires caused by nature can occur due to a prolonged dry season, while those caused by humans can occur due to the burning of forests to open land for new plantations. Land and forest fires can also be detected, as mentioned above, using the air pollution standard index (ISPU). This research examines the effect of forest and land fires on the level of air pollution, which focused on examining the particulate (PM10). The method used is simple linear regression, which is an equation that can describe the relationship between dependent variables and independent variables. The results of simple linear regression analysis are Y=26,605+8,99E-5X, and with a confidence level of 95%, the area of Forest and Land Fires (Ha) Province in Indonesia in 2019 (X) has a significant effect on the average particulate matter (PM10) of Province in Indonesia in 2019 (Y).